Effect of anti-prolactin drug and peppermint on broodiness, laying performance and egg quality in indigenous hens - Banu, Mst Nasrin; Rashid, Md Bazlar; Hasan, Md Mahmudul; Aziz, Fahima Binte; Islam, Md Rakibul; Haque, Md Anowarul (Asian Journal of Medical and Biological Research, 2017)
The study was conducted to determine the effect of antiprolactin drug (Bromergon®) and Peppermint (Mentha piperita L.) on broodiness, laying performance and egg quality in indigenous hens. The effect of modulation of prolactin concentration on egg production, sequence length and inter sequence pauses were studied by analyzing the oviposition records. Total sixty indigenous laying hens (30-40 weeks of age), were assigned for treatment with peppermint solution and Bromergon®. Sixty laying hens were randomly divided into 4 groups (A, B, C and D) and each group remained 15 hens. Group A was kept for control, Group B was treated with bromocriptine (Bromergon® SANDOZ) orally @ 640 ?g per bird per day, Group C with 50% peppermint solution @ 10 g per bird orally and Group D was with peppermint and Bromergon® combined at previous dose. Over the course of trial, incremental dietary peppermint (Group C) significantly (p?0.05) increased egg production, body weight of treated indigenous hens than other groups. Egg shell percentage, thickness and haugh unit of hens fed diets supplemented with peppermint were greater than that of hens fed the control diet. However, peppermint supplementation did not influence other egg quality characteristics like albumen and yolk percentages and albumen height. The treated birds had comparatively longer sequences and fewer pauses. It is concluded that the physiological pauses occur during ovulatory sequences can be disrupted effectively using Bromergon® and peppermint. Prolactin levels modulated which may interfere with follicular recruitment and subsequent oviposition thereby improves egg laying potential of the indigenous hens. Asian J. Med. Biol. Res. December 2016, 2(4): 547-554